0170 Shifting to Earlier Sleep Times during Sleep Extension: The Impact on Total Sleep Time and Self-Reported Fatigue and Stress. (27th April 2018) - Skeiky, L; Chownowski, J; St Pierre, M; Carlsson, K E; Mantua, J; Burke, T; Alger, S; Prindle, N E; Ratcliffe, R; Balkin, T; Capaldi, V F; Simonelli, G; et al.
Abstract: Introduction: Sleep extension is associated with a positive impact on immune function, cognitive performance, and mood. However, it also requires either an earlier bedtime, later arise time, or both. In this study, we utilized natural variability in sleep bedtimes in a healthy population participating in a 7-day sleep extension paradigm to explore the impact of shifting bedtimes. Methods: Twenty-seven healthy adults (20–39 yrs) participated in a two-phase study. During Phase 1, habitual bedtimes were recorded via actigraphy at home for two weeks. Phase 2 consisted of an in-lab portion with two conditions: 1) Sleep Extension: 7 consecutive nights (2100 bedtime, 10h time-in-bed), and 2) Sleep Deprivation (40h of total deprivation). Sleep shift times were assessed by quantifying the degree to which habitual bedtimes were shifted to 2100 in the sleep extension condition. Self-reported fatigue and stress were assessed using the Fatigue Visual Analogue Scale (FVAS) and Stress Visual Analogue Scale (SVAS). Results: Greater shifts in habitual bedtime was associated with higher self-reported fatigue (but not stress [r=0.19, p=0.34]) after one subsequent night of sleep deprivation (r=0.41, p=0.03). Sleep shift time was not linked to total sleep time (TST) during the sleep extension phase (r=-0.20, p=0.32). Additionally, sleep shift time was not correlated with self-reported fatigue (r=0.42, p=0.83) or stress (r=0.05, p=0.82) after 7 nights of sleep extension. Conclusion: Shifts in habitual bedtimes do not appear to impact total sleep time or self-reported fatigue and stress in healthy adults undergoing sleep extension in a laboratory setting. However, we found that greater shifts in habitual bedtimes prior to sleep manipulation were associated with greater self-reported fatigue after a night of sleep deprivation. These results suggest that shifting bedtimes may have an impact on fatigue that is unmasked during sleep deprivation. Support (If Any): Department of Defense Military Operational Medicine Research Program (MOMRP).